Outcome and mortality analysis in complicated parapneumonic effusion and empyema - Veerappan Periasamy, Arivudainambi (International Journal of Clinical Trials, 2017)
Background: Pleural infection is a clinical problem with high mortality and morbidity; 20% of patients with empyema die and approximately 20% require surgery to recover within 12 months of their infection. Studies on pleural infection and their outcome are relevant in developing a scoring system by which failing cases and cases at risk of death can be identified. Methods: The study is retrospective analysis of patient cohort admitted to the tertiary care institute from the period of July 2014 to July 2016 to determine the prognostic factors in the outcome of pleural space infection. The study included all complex, complicated parapneumonic effusion and empyema including tuberculosis above the age of fifteen years. The primary end of the present study was the success or failure. Possible predicting factors for the success or failure of therapy were assessed against this end. Pearson chi square test, χ2 (Fisher’s exact test when needed) test was used for discrete data. Logistic regression analysis was applied to adjust for confounding variables to assess the possible predicting factors. Survival plot and analysis using Kaplan Meier method was used. Results: 220 with parapneumonic effusion and empyema were analyzed. Successful outcome was seen in 107 and 113 had failed outcome. Mortality was 30.50%. By logistic regression method the odds of failed outcome were high with diabetes, hypoalbuminemia, loculation, tuberculosis which can predict the outcome especially complicated and complex parapneumonic effusion, empyema (p<0.05). Conclusions: Diabetes, hypoalbuminemia, loculation, tuberculosis should be used in the prediction scoring system.